COVID-19 related admissions to a regional burn center: The impact of shelter-in-place mandate - Felicia N. Williams; Lori Chrisco; Rabia Nizamani; Booker T. King (Elsevier, 2020)
The ramifications from the 2019 severe acute respiratory syndrome coronavirus 2 (COVID-19) pandemic caused by the novel corona virus will be felt globally for years to come. Mandates to shelter-in-place were called in nearly every state to limit viral exposure. The impact of the mandate on acute burn admissions was unknown. Our objective was to assess the impact of a shelter-in-place order on acute burn admissions at our burn center. All patients admitted to the burn center with burn injuries- including inhalation injury only- and desquamating skin disorders between March 10th to May 22nd, 2020 were eligible for inclusion. We compared all burn center admissions to a month-matched historical cohort from 2019, and summertime admissions for the last five years. Statistical significance was accepted as p < 0.05. There was a 9% increase in pediatric admissions after the shelter-in-place order. Compared to the 2019 cohort, there was a 28% increase in admissions of school aged children in 2020. This was not statistically significant. While the purpose of the "shelter-in-place" mandate was to reduce viral transmission of COVID-19, it consequently led to an increased percentage of admissions of school age children- comparable to our summertime numbers. More outreach and education are needed to provide safe resources for families during this pandemic.